Expressive Arts Therapy for Indonesian Nursing Students: A Mixed-Methods Evaluation of Self-Esteem and Catharsis - Dias, Maria Frani Ayu Andari; Maratning, Anastasia; Rolando, Ferry; Budianto, Zhulfikri (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2025)
Nursing education can negatively impact students' psychological well-being and self-esteem. While Expressive Arts Therapy (EAT) is a promising intervention, research on its effectiveness using hybrid methods in non-Western contexts like Indonesia is limited. This study evaluated a free-drawing-based EAT intervention to enhance the self-esteem of Indonesian nursing students. This mixed-methods study used a quasi-experimental, one-group pre-test-post-test design. From 415 students screened in South and Central Kalimantan, 24 participants with low-to-medium self-esteem were selected (purposive sampling). Data were collected using the Nurses' Self-Concept Questionnaire (NSCQ) pre- and post-intervention. Quantitative data were analyzed using a paired-samples t-test; qualitative data from in-depth interviews and FGDs (10 participants) were thematically analyzed. Quantitatively, the increase in mean self-esteem scores was not statistically significant (t(23) = -0.850, p = .202). In stark contrast, qualitative analysis revealed substantial benefits across four themes: (1) enhanced self-insight and awareness; (2) emotional catharsis and stress reduction; (3) drawing as vital non-verbal expression; and (4) a positive therapeutic experience. Although the EAT intervention did not yield statistically significant improvement in self-esteem scores, it provided profound psychological benefits like emotional catharsis and enhanced self-awareness. EAT is a valuable tool for supporting nursing students' mental well-being, functioning as an effective method for stress management and self-exploration.